"Linkedin Is My Office; Facebook My Living Room, Twitter the Neighborhood Bar": Media Scholars' Liminal Use of Social Media for Peer and Public Communication. (July 2017) - LaPoe, Victoria L.; Carter Olson, Candi; Eckert, Stine
This study grounds 45 interviews with media scholars in liminality theory and analyzes how scholars use social media as they transition to combined offline and online communication. Scholars employ highly personal strategies to decide if and how to integrate social media into their professional lives for peer and public communication. Scholars struggle with a double bind of needing to be social media savvy while worrying about career consequences of posting publicly. Few best practices exist.